Impacto da asma no Brasil : análise longitudinal e geográfica de uma base de dados governamental - Cardoso, Thiago de Araujo (2016)
Introduction: asthma is a chronic disease that affects about of 20,000,000 people in Brazil, representing the third cause of hospitalization in the country. Disease impact data are scarce in the country, but are essential for better management in public health with consequent better control of the disease in the population. Objective: The aim of our study is to present a longitudinal official data about the impact of asthma in Brazil from 2008 to 2013. Methods: We performed a descriptive study from a Brazilian government database (DATASUS), analyzing hospitalizations, the number of deaths from asthma (between 2008 and 2013), and cost of admissions, with a geographical sub-analysis. Results: In the last year analyzed, 2047 people died from asthma in Brazil (5 deaths/day), with more than 120 000 hospitalizations/year. In the whole period analyzed, the absolute number of deaths and hospitalizations decreased 10% and 36%, respectively. However, the mortality rate in hospitalized patients increased by approximately 25% in this period. Analyzing the different regions of the country, the North/Northeast and Southeast regions have the highest rates of hospitalizations for asthma and deaths of hospitalized patients, respectively. When we evaluated representative states of the regions, we also observed discrepancies in hospitalization numbers and percentage of deaths among patients hospitalized. Finally, in the studied period, hospitalizations cost US$ 170 million to the public health system. Conclusions: Although the number of hospitalizations for asthma has decreased in Brazil since 2009, mortality rates have increased, with high budget costs, showing the importance of the burden of asthma in middle-income countries.